Literasi Anak Usia Dini Melalui Alat Permainan Edukasi (APE) Ice Cream Di TK Galilea Hosanna Kids - Manulang, Rasmi; Simanjuntak, Vitalia Hanako Murni; Humaida Hanim; Simanjuntak, Markus Doddy; Sinaga, Plora Novita; Maswita (English Lecturers and Teachers Association (ELTA), 2023)
Program